CONKO-006: A randomised double-blinded phase IIb-study of additive therapy with gemcitabine + sorafenib/placebo in patients with R1 resection of pancreatic cancer – Final results. (October 2020) - Sinn, M.; Liersch, T.; Riess, H.; Gellert, K.; Stübs, P.; Waldschmidt, D.; Lammert, F.; Maschmeyer, G.; Bechstein, W.; Bitzer, M.; Denzlinger, C.; Hofheinz, R.; et al.
Abstract: Background: CONKO-006 was designed for patients with pancreatic adenocarcinoma with postsurgical R1 residual status to evaluate the efficacy and safety of the combination of gemcitabine and sorafenib (GemSorafenib) compared with those of gemcitabine + placebo (GemP) for 12 cycles. Patients and methods: This randomised, double-blind, placebo-controlled, multicenter study was planned to detect an improvement in recurrence-free survival (RFS) from 42% to 60% after 18 months. Secondary objectives were overall survival (OS), safety and duration of treatment. Results: 122 patients were included between 02/2008 and 09/2013; 57 were randomised to GemSorafenib and 65 to GemP. Patient characteristics were wellbalanced (GemSorafenib/GemP) in terms of median age (63/63 years), tumour size (T3/T4: 97/97%), and nodal positivity (86/85%). Grade 3/4 toxicities comprised diarrhoea (GemSorafenib: 12%; GemP: 2%), elevated gamma-glutamyl transferase (GGT) (19%; 9%), fatigue (5%; 2%) and hypertension (5%; 2%), as well as neutropenia (18%; 25%) and thrombocytopenia (9%; 2%). By August 2017, 118 (97%) RFS event had occurred. There were no difference in RFS (median GemSorafenib: 8.5 versus GemP: 9.4 months; p = 0.730) nor OS (median GemSorafenib: 17.6 versus GemP: 17.5 months; p = 0.481). Landmark analyses suggest that patients who received more than six cycles of postoperative chemotherapy had significantly longer OS (p = 0.021). Conclusion: CONKO-006 is the first randomised clinical trial to include exclusively patients with PDAC with postsurgical R1 status thus far. Sorafenib added to gemcitabine did neither improve RFS nor OS. However, postoperative treatment exceeding six months seemed to prolong survival and should be further investigated in these high-risk patients. Clinical trial information: German Tumor Study Registry (Deutsches Krebsstudienregister), DRKS00000242. Highlights: Patients with R1 resection of pancreatic ductal adenocarcinoma (PDAC) relapsed in more than 90%. Gemcitabine + sorafenib is not effective in the postoperative treatment of PDAC. Adjuvant gemcitabine exceeding 6 months may be beneficial in R1-resected PDAC not suitable for mFOLFIRINOX.